Understanding performance deficits in developmental coordination disorder: a meta-analysis of recent research - Wilson, Peter H.; Blank, Rainer (Developmental medicine and child neurology, 2013)
Aim Developmental coordination disorder (DCD) is a significant disorder of childhood, characterized by core difficulties in learning fine and/or gross motor skills, and the attendant psychosocial problems. The aim of the meta-analysis presented here (the first on DCD since 1998) was to summarize trends in the literature over the past 14 years and to identify and describe the main motor control and cognitive deficits that best discriminate children with DCD from those without. Method A systematic review of the literature published between January 1997 and August 2011 was conducted. All available journal papers reporting a comparison between a group of children with DCD and a group of typically developing children on behavioural measures were included. Results One hundred and twenty-nine studies yielded 1785 effect sizes based on a total of 2797 children with DCD and 3407 typically developing children. Across all outcome measures, a moderate to large effect size was found, suggesting a generalized performance deficit in children with DCD. The pattern of deficits suggested several areas of pronounced difficulty, including internal (forward) modelling, rhythmic coordination, executive function, gait and postural control, catching and interceptive action, and aspects of sensoriperceptual function. Interpretation The results suggest that the predictive control of action may be a fundamental disruption in DCD, along with the ability to develop stable coordination patterns. Implications for theory development and intervention are discussed.